The Human Postsynaptic Density Shares Conserved Elements with Proteomes of Unicellular Eukaryotes and Prokaryotes - Emes, Richard D.; Grant, Seth G. (Frontiers in Neuroscience, 2011)
The animal nervous system processes information from the environment and mediates learning and memory using molecular signaling pathways in the postsynaptic terminal of synapses. Postsynaptic neurotransmitter receptors assemble to form multiprotein complexes that drive signal transduction pathways to downstream cell biological processes. Studies of mouse and Drosophila postsynaptic proteins have identified key roles in synaptic physiology and behaviour for a wide range of proteins including receptors, scaffolds, enzymes, structural, translational and transcriptional regulators. Comparative proteomic and genomic studies identified components of the postsynaptic proteome conserved in eukaryotes and early metazoans. We extend these studies, and examine the conservation of genes and domains found in the human postsynaptic density with those across the three superkingdoms, archaeal, bacteria and eukaryota. A conserved set of proteins essential for basic cellular functions were conserved across the three superkingdoms, whereas synaptic structural and many signaling molecules were specific to the eukaryote lineage. Genes involved with metabolism and environmental signaling in E. coli including the chemotactic and ArcAB Two-Component signal transduction systems shared homologous genes in the mammalian post-synaptic proteome. These data suggest conservation between prokaryotes and mammalian synapses of signaling mechanisms from receptors to transcriptional responses, a process essential to learning and memory in vertebrates. A number of human postsynaptic proteins with homologues in prokaryotes are mutated in human genetic diseases with nervous system pathology. These data also indicate that structural and signaling proteins characteristic of postsynaptic complexes arose in the eukaryotic lineage and rapidly expanded following the emergence of the metazoa, and provide an insight into the early evolution of synaptic mechanisms and conserved mechanisms of learning and memory.